Increased arterial stiffness parameters in panic disorder patients in long term treatment period. Issue 1 (December 2016) - Yanartas, Omer; Sunbul, Murat; Senkal, Zeynep; Durmus, Erdal; Kivrak, Tarik; Subasi, Nilufer; Karaer, Gulhan; Ergun, Serhat; Sari, Ibrahim; Sayar, Kemal
Abstract Background The relationship between mental stress and cardiovascular disease has been shown in several studies. Panic disorder (PD) is also associated with cardiovascular disease due to increased risk of myocardial infarction. The aim of this study is to evaluate the association between arterial stiffness parameters and depression/anxiety scores in patients with PD. Methods The study population consisted of 25 patients with PD and 25 age–sex-matched healthy controls. Depression and anxiety levels were evaluated by Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI), respectively. Determination of arterial stiffness parameters was conducted using a Mobil-O-Graph arteriograph system that detected signals from the brachial artery. Results While baseline characteristics were similar between two groups, BDI and BAI scores were significantly higher in patients with PD (p  < 0.005). The pulse wave velocity (PWV) and Augmentation Index (AIx) were also significantly higher in patients with PD (p  = 0.001, p  = 0.006). There was a moderate correlation between PWV and AIx with BAI scores (r  = 0.442, p  = 0.001, r  = 0.441, p  = 0.001). AIx was also positively correlated with BDI scores (r  = 0.415, p  = 0.03). Conclusion We demonstrated a significant relationship between arterial stiffness parameters and anxiety/depression scores in patients with PD who receive antidepressant treatment.